The Influence Of Work Environment And Work-Life Balance On Generation Z Employee Job Satisfaction With Work Stress Mediation - Fitriani, Indria; Hasanudin, Hasanudin; Jaya, Arman (Jurnal Multidisiplin, 2025)
Generation Z is increasingly dominating the workforce, bringing unique characteristics, expectations, and challenges compared to previous generations. Therefore, gaining a deeper understanding of these factors is essential for helping organizations develop more adaptive and responsive human resource management strategies, especially in attracting, retaining, and motivating Generation Z employees. This study aims to analyze the influence of the work environment and work-life balance on the job satisfaction of Generation Z, with work stress considered as a mediating variable. The population of this study includes individuals from Generation Z with work experience in various sectors in West Kalimantan. The sample consists of 130 Generation Z employees. The research employs Structural Equation Modeling (SEM) using the SmartPLS 4 statistical software to assess the validity of the measurement model and the relationships among variables in the structural model. The results reveal that both the work environment and work-life balance positif and significantly affect job satisfaction. Furthermore, work stress is shown to play a significant mediating role in this relationship. These findings offer important implications for organizations seeking to create supportive work conditions for Gen Z  in the modern work era.